Functionalization of Scanning Probe Tips with Epitaxial Semiconductor Layers. Issue 3 (5th January 2017) - Giliberti, Valeria; Sakat, Emilie; Bollani, Monica; Altoe, M. Virginia; Melli, Mauro; Weber‐Bargioni, Alexander; Baldassarre, Leonetta; Celebrano, Michele; Frigerio, Jacopo; Isella, Giovanni; Cabrini, Stefano; Ortolani, Michele
Abstract : Functionalized scanning probe tips hold great promise for the controlled delivery of signals from and to selected nanoscale volumes. Here, a new nanotechnological approach for the functionalization of scanning probe tips is presented, targeting the transfer of the optical, electrical, thermal, or chemical properties of precisely characterized epitaxial semiconductor layers to the nanoscale probe tip. Homogeneously doped, strain‐relaxed heteroepitaxial germanium layers, several micrometers thick, are first grown on silicon wafers by low‐energy plasma‐enhanced chemical vapor deposition and then employed to functionalize the probe apex. This choice of materials and growth technique enables the future scalability of the tip functionalization process toward high production volumes. The fabricated probe tips are investigated in a transmission electron microscope, revealing that the crystal structure and the homogeneous doping level of the epitaxial layers are unchanged after the probe‐tip functionalization process. These doped‐germanium tips are also tested as nanoemitters of light at telecom wavelengths (1.55 µm) and applied as scattering probes for near‐field mid‐infrared microscopy. The reported combination of heteroepitaxial growth and a nanofabrication approach can be extended to a variety of epitaxial materials, thus enabling a new generation of scanning probes for the investigation of nanostructured materials and devices. Abstract : Scanning probe tips are functionalized by a novel method, which is presented with the aim of exploiting the unique properties of epitaxial semiconductor layers for nanoimaging and nanospectroscopy. In this demonstration, the epitaxial Ge material is extracted by a lift‐out process from Ge‐on‐Si films patterned into micropillars, directly employing an atomic force microscopy cantilever probe.